2015
DOI: 10.4138/atlgeol.2015.006
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic and temporal context and faunal diversity of Permian-Jurassic continental tetrapod assemblages from the Fundy rift basin, eastern Canada

Abstract: <p style="margin: 1em 0px; line-height: 200%; text-indent: 0.5in;"><span style="font-family: 'Minion Pro','serif'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-CA;"><span style="font-size: medium;">The Fundy basin in Nova Scotia and New Brunswick is the largest exposed rift basin of the Newark Supergroup and also extends beneath the Bay of Fundy. Its strata can be divided into four tectonostratigraphic sequences (TS). TS I is represented by the probably Permian Honeycomb Poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 95 publications
3
64
0
Order By: Relevance
“…A clade formed by Hyperodapedon sanjuanensis and the Nova Scotia (Baird, 1963; Sues & Olsen, 2015) plus Wyoming (Lucas, Heckert & Hotton III, 2002) forms has also been recovered (Fig. 10), matching previous suggestions in the literature (Chatterjee, 1980; Lucas, Heckert & Hotton III, 2002; Mukherjee & Ray, 2014).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…A clade formed by Hyperodapedon sanjuanensis and the Nova Scotia (Baird, 1963; Sues & Olsen, 2015) plus Wyoming (Lucas, Heckert & Hotton III, 2002) forms has also been recovered (Fig. 10), matching previous suggestions in the literature (Chatterjee, 1980; Lucas, Heckert & Hotton III, 2002; Mukherjee & Ray, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…Also, this generalization can be hinted for units with a less abundant fossil record, but with members of the “ Hyperodapedon clade” as one of the recognized taxa, such as the Popo Agie and Pebbly Arkose formations, the Evangeline Member of the Wolfville Formation, as well as the here discussed (see above) Mahogo Formation. Indeed, as for the best known North American strata, a recent and comprehensive review of the Fundy Rift Basin (Sues & Olsen, 2015) gathered evidence of an agreeing late Carnian age for the Evangeline Member of the Wolfville Formation, which yielded the Nova Scotia form, and a similar age has also been hinted for the Popo Agie Formation (Hartman, Lovelace & Stocker, 2015), which yielded the Wyoming form. Radiosisotpic dates are still missing for the Tiki, lower part of the Maleri, and Lossiemouth Sandstone formations, but these could test the validity of Hyperodapedon as a late Carnian (Tuvalian) index fossil.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, the skull of the sphenodontian reptile Clevosaurus bairdi from Wasson Bluff (Sues et al 1994) is virtually indistinguishable from that identified as Clevosaurus sp. from an unidentified locality in the "Stormberg Group" of southern Africa (Sues and Reisz 1995) and that of Clevosaurus brasiliensis from the Caturrita Formation (Late Triassic: Norian) of Brazil (Bonaparte and Sues 2006). First described from Late Triassic fissure-fillings in southwestern England (Fraser 1988), Clevosaurus has also been reported from the Lower Jurassic Lower Lufeng Formation of Yunnan, China (Jones 2006) and Early Jurassic fissure-fillings in Wales (Säilä 2005).…”
Section: Significance Of the New Materialsmentioning
confidence: 93%